Unmasking a role for sex chromosomes in gene silencing - Maatouk, Danielle M (BioMed Central, 2010)
Several sexually dimorphic phenotypes correlate with sex-chromosome dosage rather than with phenotypic sex. New research suggests that sex chromosome dimorphism helps to regulate gene silencing.